Radial expansion approach and its mechanism to reduce residual stress and distortion of girth joint structure. (October 2021) - Zhao, Tianyi; Zhao, Yue; Wu, Aiping; Wang, Guoqing; Yan, Dongyang; Wan, Zhandong; Wu, Huiqiang
Abstract: In this study, a radius expansion approach to enlarge radius around welding area is proposed to reduce residual stresses and distortion for large girth joint structure. The finite element (FE) model is developed to investigate the effects of expansion on the welding residual stresses and distortion. The simulation is verified with the experiment results. With larger radius expansion, there is lower residual stresses and distortion in joint. The mechanism is discussed using thermal-elastic-plastic (TEP) strains theory of welding. The theoretical analysis reveals that elastic strain induced by radius expansion is the key factor that reduces hoop residual stress and radial shrinkage.